Spectroscopic Analysis of CdO1-X: SnX Plasma Produced by Nd:YAG Laser - Khalaf, Madyan A.; Ahmed, Baida M.; Aadim , Kadhim A. (Iraqi Journal of Science, 2020)
In this work, the optical emission spectrum technique was used to analyze the spectrum resulting from the CdO:Sn plasma produced by laser Nd:YAG with a wavelength of (1064) nm, duration of (9) ns, and a focal length of (10) cm in the range of energy of 500-800 mJ. The electron temperature (Te) was calculated using the in ratio line intensities method, while the electron density (ne) was calculated using Saha-Boltzmann equation. Also, other plasma parameters were calculated, such as plasma (fp), Debye length (Î»D) and Debye number (ND). At mixing ratios of X=0.1, 0.3 and 0.5, the CdO1-X :SnX plasma spectrum was recorded for different energies. The changes in electron temperature and the densities were studied as a function of the laser energies. Outcome measure value of the electron temperature at the ratio of X = 0.1 was (1.079-1.054) eV, while at X=0.3 the Te range was (0.952- 0.921) eV and at X=0.5 it was (0.928-0.906) eV.